Effectiveness of formic acid and thymol in the control of Varroa destructor in africanized honey bee colonies - Calderón, Rafael A. (2014)
The effectiveness of formic acid and thymol in the control of the mite Varroa destructor was evaluated from June to October 2011 in an apiary of 16 Africanized honeybee colonies (the colonies did not receive chemical treatment at all) located in Atenas, Alajuela. The apiary was randomly divided in three groups (A, B and C) of 8, 5 and 3 colonies, respectively. Group A was treated with 150 g of formic acid at 65%, group B received 2 applications of 25 g thymol and colonies of group C were used as control. Varroa traps were placed on the bottom board of each colony to collect the mites. After 4 weeks, all colonies were treated with 4 strips of flumethrin to kill the remaining mites and to assess the effectiveness of the products. Furthermore, the mortality of the different stages of varroa was evaluated in capped worker brood cells checking the pupa and the bottom of the cell for mites. The effectiveness of formic acid and thymol in the control of varroa mites was 94.7% and 96.9% respectively. In colonies treated with formic acid varroa mortality occurred mainly during 72 h after application, meanwhile in the roup treated with thymol the mite mortality was observed mainly one week after treatment. In addition, in the group of colonies treated with formic acid 86% of mite mortality occurred in capped brood cells, while in colonies treated with thymol and control colonies the varroa mortality in capped cells was less than 10%. In conclusion, the effectiveness of formic acid and thymol in the control of varroa mites was high, for which reason both products can be considered an alternative for the integrated management of varroa mites in Africanized honeybees colonies.